Research and building kinematic model for transverse system of the motion platform on specialized vehicles - Chu, Đức Chình; Nguyễn Đức Thọ; Phạm Trường Giang (Journal of Military Science and Technology, 2023)
Stabilization system on specialized vehicles allows the motion platform type pan-tilt system to be stabilized in horizontal and vertical planes while the vehicle is on moving. Therein, the transverse system is an electric-drive one using a separated excitor DC motor and the power element is an electromagnetic amplifier. In this paper, the research results in order to build a kinematic model for the system based on the physical relationships and experimental results are presented. Then, an algorithm control is proposed to improve the quality of platform stabilization in the horizontal plane. These results are simulated to prove the correctness of the model and the effectiveness of the proposed algorithm.